Knowledge and perception of guardians towards general danger: Signs in under-five children at Kamuzu Central Hospital - Nkhoma, Yamikani Bridget (Kamuzu University of Health Sciences, 2022)
Children, especially the very young are susceptible to illness and have a higher mortality rate than older children They commonly present with general danger signs such as convulsions, lethargy, chest in-drawing, irritability and others. General danger signs are signs which indicate that a child is having a life threatening condition requiring urgent hospital attention .Most children with a general danger sign need urgent hospital care and they may need life saving treatment with injectable antibiotics, oxygen therapy or other treatments which may not be available at home. General danger signs are non specific signs that do not point out to a particular problem. This study was aimed at finding out knowledge and perception of guardians towards general danger signs in under-five children at Kamuzu Central hospital. The study was a qualitative in nature and it used ten guardians as participants . In depth interviews were done to collect data using an interview guide. The findings of the study indicated that guardians have little knowledge on general danger signs . They believe that general danger signs come as a result of witchcraft and promiscuity behavior of the parents. it also revealed that most guardians first treat their children with traditional medicine or a combination of traditional medicine with over the counter drugs. Basing on the findings, the researcher recommend that health workers need to educate guardians on general danger signs to increase awareness of the general danger signs so that child mortality rate can be reduce to achieve the millennium goal number three